2009
DOI: 10.2478/s11535-008-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel neuroprotectant PAN-811 protects neurons from oxidative stress

Abstract: Abstract:Hydrogen peroxide (H 2 O 2 ), a major non-radical reactive oxygen species (ROS) could elicit intracellular oxidative damage and/or cause extracellular free calcium influx by activating the NMDA receptor or through calcium channels. In the present study, NMDA receptor antagonist MK-801 fully blocked H 2 O 2 -induced neuronal cell death, whereas green tea (GT) extract containing-antioxidants only partially suppressed the neurotoxicity of H 2 O 2 . These suggest that majority of ROS overproduction is dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Significantly different than that of the H 2 O 2 -treated group: *p50.05; **p50.01. brain during the progress of AD (Pan et al 2009). The pre-treatment of the cells with the extract from C. tamariscifolia and C. nodicaulis enhanced cell survival up to almost 100% compared with the H 2 O 2 -treated group, which had a viability of 53.4% (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly different than that of the H 2 O 2 -treated group: *p50.05; **p50.01. brain during the progress of AD (Pan et al 2009). The pre-treatment of the cells with the extract from C. tamariscifolia and C. nodicaulis enhanced cell survival up to almost 100% compared with the H 2 O 2 -treated group, which had a viability of 53.4% (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, our previous study revealed that PAN-811 can inhibit ischemic or hypoxic neurotoxicity to post-mitotic neurons by scavenging free radicals and suppressing OS [ 31 ]. PAN-811 has been shown to protect neurons from H 2 O 2 -induced cell death [ 32 , 33 ] as well.…”
Section: Discussionmentioning
confidence: 99%
“…PAN-811, chemical name 3-aminopyridine-2-carboxaldehyde thiosemicarbazone (3-AP, also called Triapine), is a ribonucleotide reductase inhibitor, originally designed for cancer therapy [ 23 25 ] and tested in Phase 1 and 2 clinical trials with a favorable safety profile [ 26 30 ]. PAN-811 has shown a capability of scavenging stable free radicals in a cell-free environment, and the ability to inhibit H 2 O 2 -induced neurotoxicity [ 31 33 ]. We have recently demonstrated that PAN-811 blocks OS-dependent in vitro neurotoxicity of 5-FU or MTX [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neurons that were treated with PAN-811 looked to have a healthy appearance even when they were insulted with MTX, 5-FU, or CDDP. Our previous studies have demonstrated that, besides inhibiting excitatory neurotoxicity, PAN-811 can protect neurons from cell death under different OS-involved conditions, such as hypoxia [ 22 ], and hydrogen peroxide insult [ 14 , 15 ]. In a cell-free and metal-free system, PAN-811 demonstrated an activity in direct scavenging of stable radical diphenylpicrylhydrazyl (DPPH) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…MTX can also cross the blood-brain barrier as well [ 11 ] and result in an increase of OS in cerebral spinal fluid and executive dysfunction in MTX-treated patients of pediatric acute lymphoblastic leukemia [ 12 , 13 ]. It is well known that ROS, such as H 2 O 2 , can result in neuronal cell death [ 14 , 15 ]. Cisplatin (CDDP) is an alkylating agent.…”
Section: Introductionmentioning
confidence: 99%